2005
DOI: 10.1083/jcb.200411060
|View full text |Cite
|
Sign up to set email alerts
|

CDK4 regulation by TNFR1 and JNK is required for NF-κB–mediated epidermal growth control

Abstract: Nuclear factor κB (NF-κB) mediates homeostatic growth inhibition in the epidermis, and a loss of NF-κB function promotes proliferation and oncogenesis. To identify mechanisms responsible for these effects, we impaired NF-κB action in the epidermis by three different genetic approaches, including conditional NF-κB blockade. In each case, epidermal hyperplasia was accompanied by an increase in both protein levels and tissue distribution of the G1 cell cycle kinase, CDK4. CDK4 up-regulation required intact TNFR1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 31 publications
3
57
0
Order By: Relevance
“…Furthermore, inhibition of NF-kB activity combined with expression of oncogenic Ras in epidermal keratinocytes leads to invasive neoplasia with features similar to those of squamous cell carcinoma (Dajee et al, 2003). More recent studies have revealed that RelA-deficient skin manifests hyperplasia in absence of apoptosis, inflammation or abnormal differentiation and that this depends on TNF-R1-dependent activation of the JNK signaling pathway and activation of the cell cycle kinase CDK4 (Zhang et al, , 2005. Consequently, it seems that NF-kB can adopt tumorpromoting or tumor-suppressor roles in different cell types.…”
Section: Nf-jb and Programmed Cell Death J Dutta Et Almentioning
confidence: 99%
“…Furthermore, inhibition of NF-kB activity combined with expression of oncogenic Ras in epidermal keratinocytes leads to invasive neoplasia with features similar to those of squamous cell carcinoma (Dajee et al, 2003). More recent studies have revealed that RelA-deficient skin manifests hyperplasia in absence of apoptosis, inflammation or abnormal differentiation and that this depends on TNF-R1-dependent activation of the JNK signaling pathway and activation of the cell cycle kinase CDK4 (Zhang et al, , 2005. Consequently, it seems that NF-kB can adopt tumorpromoting or tumor-suppressor roles in different cell types.…”
Section: Nf-jb and Programmed Cell Death J Dutta Et Almentioning
confidence: 99%
“…Wang et al, have demonstrated that NF-κB functions as a positive modulator of cellular senescence, an intrinsic tumor suppression mechanism, by showing that human fibroblasts lacking NF-κB activity prematurely exit from senescence [63]. Others have shown that skin cells devoid of NF-κB activity exhibit deregulated growth correlating with impaired cell-cycle control [64,65]. It has been proposed that the role of NF-κB in cellular senescence could be cell type specific, differentially initiating senescence or acting further downstream in the DNA repair process to maintain the senescent state [2,63].…”
Section: Nf-κb and The Dna Repair Processmentioning
confidence: 99%
“…Cross-talk between NF-κB and p53 has been established by multiple groups ( [75,76]; see review [77]), including results that suggest NF-κB may have both anti-and proapoptotic roles. Only a limited number of studies have investigated the role of NF-κB in DNA damage and repair in skin cells (including: [64,65,78,79,80,81] [81], a process that was crucial in order to eradicate the cells that bear the risk of becoming tumorigenic. In HaCat keratinocytes, hydroxytyrosol (main component of olive oil shown to be an inhibitor of NF-κB), has been shown to significantly reduce the DNA strand breaks caused by UVB, and also attenuate the expression of p53 and NF-κB in a concentrationdependent manner [78].…”
Section: Nf-κb and The Dna Repair Processmentioning
confidence: 99%
“…Mouse epidermis and E14.5 keratinocytes deficient for p65/RelA display marked hyperplasia/proliferation, increased levels of active, nuclear c-jun NH 2 -terminal kinase (JNK1/2), and a significant increase in protein levels of cyclin-dependent kinase 4 (CDK4) (Zhang et al, 2004(Zhang et al, , 2005. JNK, a member of the MAP kinase family, is activated by tumor necrosis factor cell surface receptor, TNFR1 (as is NF-B), and participates in numerous cellular processes, including proliferation (reviewed in Aggarwal, 2000;Ghosh and Karin, 2002).…”
Section: Nf-b-on the Same Team As Notchmentioning
confidence: 99%
“…The hyperplasia observed in p65/ RelA Ϫ/Ϫ epidermis was shown to be dependant on intact TNFR1, and increased JNK and CDK4 activity. p65/RelA Ϫ/Ϫ, TNFR Ϫ/Ϫ epidermis lacked hyperplasia and displayed normal levels of CDK4 (Zhang et al, 2005) and JNK (Zhang et al, 2004). Pharmacological treatment of p65/RelA-deficient epidermis with a topical JNK inhibitor decreased levels of activated JNK and reversed the epidermal hyperplasia (Zhang et al, 2004).…”
Section: Nf-b-on the Same Team As Notchmentioning
confidence: 99%